Roma as a political identity: Exploring representations of Roma in Europe. (December 2014) - McGarry, Aidan
This article explores some of the myriad representations of Roma in Europe and argues that this proliferation makes it more difficult for policymakers to formulate coherent interventions, for academics to agree on a common conceptual language and for the majority to understand the inter-connected problems facing Roma communities. 'Representations' refers to how the community is understood by itself as well as by others. Whilst no community retains an uncontested image of itself and its identity, Roma communities have little or no control over how they are represented in the public sphere. Usually, representations of Roma originate and are sustained by non-Romani actors including international organisations, national governments and the majority. Of course, Roma communities have attempted to influence how they represent themselves externally to challenge negative stereotypes and internally, to raise a political consciousness and foster solidarity. Relatedly, the political representation of Roma is particularly important due to their weak political positioning in local, national and transnational contexts but also because it highlights the disparity between contested questions of who Roma are and devising policy interventions to address socio-economic and political exclusion. This article discusses a select number of prevalent Roma representations and links the representation of Roma identity to the public presence and agency of Romani communities.